2019
DOI: 10.1002/ejsp.2561
|View full text |Cite
|
Sign up to set email alerts
|

The big two dictionaries: Capturing agency and communion in natural language

Abstract: Four studies developed and validated two dictionaries to capture agentic and communal expressions in natural language. Their development followed the Linguistic Inquiry and Word Count (LIWC) approach (Study 1) and we tested their validity with frequency‐based analyses and semantic similarity measures. The newly developed Agency and Communion dictionaries were aligned with LIWC categories related to agency and communion (Study 2), and corresponded with subjective ratings (Study 3), confirming their convergent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 76 publications
5
98
2
Order By: Relevance
“…These results supported H1, and are consistent with a previous study [16] which reported that people expect tangible information about control issues of AVs and their safety. These results are also coherent with the notion that the communion and agency are distinctly expressed in natural language [79,132]. The objective of the second study was to confirm how the recipient's safety concerns (observer's perspective) as well as goal orientation (agent's perspective) with regard to AV is related to technology acceptance components in different technology presentation contexts (the agentic vs communal AV advertisement).…”
Section: Theoretical Contributionsupporting
confidence: 74%
See 2 more Smart Citations
“…These results supported H1, and are consistent with a previous study [16] which reported that people expect tangible information about control issues of AVs and their safety. These results are also coherent with the notion that the communion and agency are distinctly expressed in natural language [79,132]. The objective of the second study was to confirm how the recipient's safety concerns (observer's perspective) as well as goal orientation (agent's perspective) with regard to AV is related to technology acceptance components in different technology presentation contexts (the agentic vs communal AV advertisement).…”
Section: Theoretical Contributionsupporting
confidence: 74%
“…The objective of the second study was to confirm how the recipient's safety concerns (observer's perspective) as well as goal orientation (agent's perspective) with regard to AV is related to technology acceptance components in different technology presentation contexts (the agentic vs communal AV advertisement). First, the pilot study provided confirmation that communal and agentic content may be utilized to create a description of AV technology [79]. People not only perceive and distinguish these types of content in themselves and others, regardless of culture [133], but also when it comes to the AV technology context.…”
Section: Theoretical Contributionmentioning
confidence: 89%
See 1 more Smart Citation
“…The procedure we used to develop and validate the PVD builds upon and advances procedures used in earlier approaches to extracting information on psychological constructs from text data, such as personality traits, moral foundations, or sentiments (Graham, Haidt, & Nosek, 2009; Pietraszkiewicz et al, 2018; Tausczik & Pennebaker, 2010). In the development stage, a group of experts agreed on a list of candidate words representing the 10 value types proposed by Schwartz (1992) (content validity).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a recent study (Pietraszkiewicz, Formanowicz, Gustafsson Sendén, Boyd, Sikstrom, & Sczesny, 2018) developed dictionaries of communion (similar to warmth) and agency (similar to competence) using the LIWC development approach. In the supplement, we further discuss these dictionaries and how they compare to the subset of dictionaries developed here for these constructs.…”
Section: Illustration: Stereotype Contentmentioning
confidence: 99%